Characteristics of the Covid-19 Pandemic in the United States, 2020 - Richard Sauerheber (Archives of Preventive Medicine - Peertechz Publications, 2020)
Time dependent changes in the number of cases of Covid-19, as well as deaths from the disease, are examined and compared to other population parameters including the magnitude of employment across the country. Associations are found that help to explain the tortuous course that the virus infection was able to cause in the U.S.